Bone density testing among prostate cancer survivors treated with androgen‐deprivation therapy12. Issue 4 (12th October 2012) - Morgans, Alicia K.; Smith, Matthew R.; O'Malley, A. James; Keating, Nancy L.
Abstract BACKGROUND. Androgen‐deprivation therapy (ADT) causes bone loss and fractures. Guidelines recommend bone density testing before and during ADT to characterize fracture risk. The authors of the current report assessed bone density testing among men who received ADT for ≥ 1 year. METHODS. Surveillance, Epidemiology, and End Results/Medicare data were used to identify 28, 960 men aged > 65 years with local/regional prostate cancer diagnosed from 2001 to 2007 who were followed through 2009 and who received ≥ 1 year of continuous ADT. Bone density testing was documented in the 18‐month period beginning 6 months before ADT initiation. Logistic regression was used to identify the factors associated with bone density testing. RESULTS. Among men who received ≥ 1 year of ADT, 10.2% had a bone density assessment from 6 months before starting ADT through 1 year after. Bone density testing increased over time (14.5% of men who initiated ADT in 2007‐2008 vs 6% of men who initiated ADT in 2001‐2002; odds ratio for 2007‐2008 vs 2001‐2002, 2.29; 95% confidence interval, 1.83‐2.85). Less bone density testing was observed among men aged ≥ 85 years versus men ages 66 to 69 years (odds ratio, 0.76; 95% confidence interval, 0.65‐0.89), among black men versus white men (odds ratio, 0.72; 95% confidence interval, 0.61‐0.86), and among men in areas with lower educational attainment (P < .001). Men who visited a medical oncologist and/or a primary care provider in addition to a urologist had higher odds of testing than men who only consulted a urologist (P < .001). CONCLUSIONS. Few men who received ADT for prostate cancer underwent bone density testing, particularly older men, black men, and those living in areas with low educational attainment. Visiting a medical oncologist was associated with increased odds of testing. Interventions are needed to increase bone density testing among men who receive long‐term ADT. Data on bone density testing for nonmilitary populations of prostate cancer survivors in the United States who have received long‐term androgen‐deprivation therapy (ADT) have not been published. The current analysis of Surveillance, Epidemiology, and End Results/Medicare data suggests that few prostate cancer survivors who receive long‐term ADT undergo bone density testing; and several key populations, including African Americans and older men, have considerably lower rates of bone density screening. Cancer 2013. © 2012 American Cancer Society.